Perilipin-2 promotes lipid droplet-plasma membrane interactions that facilitate apocrine lipid secretion in secretory epithelial cells of the mouse mammary gland - Monks, Jenifer; Orlicky, David J.; Libby, Andrew E.; Dzieciatkowska, Monica; Ladinsky, Mark S.; McManaman, James L. (Frontiers in Cell and Developmental Biology, 2022)
Secretory epithelial cells (sMEC) in mammary glands of lactating animals secrete lipids by a novel apocrine mechanism in which cytoplasmic lipid droplets (LD) contact and are enveloped by elements of the apical plasma membrane (APM) before being released into the lumen of the gland as membrane bound structures. The molecular properties of LD-APM contacts and the mechanisms regulating LD membrane envelopment and secretion are not fully understood. Perilipin-2 (Plin2) is a constitutive LD protein that has been proposed to tether LD to the APM through formation of a complex with the transmembrane protein, butyrophilin1a1 (BTN) and the redox enzyme, xanthine oxidoreductase (XOR). Using mice lacking Plin2 and physiological inhibition of apocrine lipid secretion, we demonstrate that LD-APM contact and envelopment are mechanistically distinct steps that they are differentially regulated by Plin2 and independent of LD secretion. We find that Plin2 is not required for formation of LD-APM contacts. However, it increases the percentage of LD that contact the APM and mediates enlargement of the LD-APM contact zone as LD undergo membrane envelopment. The effects of Plin2 LD-APM interactions are associated with increased abundances of BTN, XOR and Cidea, which are implicated as mediators of LD-APM contact formation, on membranes surrounding secreted LD, and with promotion of glycocalyx remodeling at LD-APM contact sites. We propose that Plin2 does not directly mediate contact between LD and the APM but acts by enhancing molecular interactions that stabilize LD-APM contacts and govern membrane envelopment of LD during apocrine lipid secretion. Plin2 does not appear to significantly affect the lipid content of milk in fully lactating animals, but it does increase lipid secretion at the onset of lactation in primaparous dams, which suggest a role in facilitating apocrine lipid secretion in sMEC during their initial transition to a secretory phenotype.